Kashmir Conflict and the Advent of Torture: An Overview - Inamul Haq (RIRAI Publisher, 2020)
Modern states have built burgeoning detention facilities like immigration centers, prisons and police cells that engage in torture and other cruel, inhuman treatments. The law enforcement agencies engage in torture and other cruel, inhuman and degrading treatment or punishment in the name of counter- terrorism, security threats and soon. The state uses torture and makes it clear that enhanced interrogation techniques makes a person from kidnapping to extra-ordinary rendition, from citizen to unlawful enemy combatant and from human to terrorist. The valley of Kashmir faces torture and other cruel inhuman treatments since insurgency began in 1990’s, with violent uprising and have elicited terrorism. Methods like torture is used as a tool of counter- insurgency by Indian security forces. The government of India used all efforts to crush the movement of self- determination of Kashmir. The strong response from India violates the human rights and international humanitarian laws. The law enforcement agencies, army and para- military forces have engaged in reprisal attacks against civilians resulting in indiscriminate firing, search operations, gang-rapes and burning of houses in the valley. After 1990, the situation in the Kashmir valley deteriorated and Kashmir was declared a disturbed area and laws like Disturbed Area Act (DAA) 1990, Armed Forces Special Powers Act (AFSPA) 1990 and Public Safety Act (PSA) 1978 were imposed. The purpose of the paper is to examine the concept of Torture in Kashmir valley and bring to light the plight of the victims in the valley.